Assessment of Some Physico-Chemical Parameters and Heavy Metals in The Greater Zab River Path from Bekhma to Al Guwayr District in Erbil Province-KRI. - Chiyai M. Shareef; Farhad H. Aziz (Zanco Journal of Pure and Applied Sciences, 2023)
Fifteen physico-chemical parameters with heavy metals were evaluated from the Greater Zab River path within Erbil province in twelve sites over a period of 10 months (from April 2021 to January 2022). In the field, Air and water temperature measured by thermometer, Electrical conductivity, total dissolved solids, potential of hydrogen measured by portable EC and pH meter, While, the laboratory measurement included total hardness, calcium ion, magnesium ion, total alkalinity, chloride measured by titration method, nitrate, nitrite, phosphorus and sulfate measured by spectrophotometric method. Water Quality calculated by using Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI). Heavy metals were analyzed by (AAS Perkins Elmer USA 1100D). The results of the present study shows that electrical conductivity, total alkalinity and phosphorus mean values were higher than the limits of WHO standards, While all remaining mean parameters were found in agreement for drinking purposes for WHO standards. The studied sites were classified under the hard waters. CCME WQI status for all sites located under the category of “Fair” (65-79) except for site 12 was located under the category of “Marginal” (45-64) water quality. The decreasing trend of heavy metals were observed in the water as Si > Fe > Cr > Zn > Mn > Pb > Ni > Co > Cu > Cd.